A Practical Approach to Clinical Antibiotic Stewardship in the ICU Patient with Severe Infection - Fierens, Jan; Depuydt, Pieter O.; De Waele, Jan J. (Seminars in Respiratory and Critical Care Medicine, 2019)
Patients with severe infections are often treated with multiple courses of antibiotics in the intensive care unit (ICU), making the ICU a true antibiotic hotspot. The increasing incidence of multidrug resistance worldwide emphasizes the need for continued efforts in developing and implementing antibiotic stewardship programs. Using a pragmatic approach for the bedside clinical team, this review will highlight different key moments for antibiotic decision making throughout the course of the antibiotic treatment in patients with severe infections. We will focus especially on the importance of adequate empirical therapy, source control in infections, assessment of immune status, and two separate antibiotic time-out moments early in the course, as well as the moment of stopping antibiotics. Additionally, the importance of a team-based approach and clinical decision support systems will be highlighted.
Keywords: antibiotic stewardship; clinical decision support systems; empirical therapy; critical illness; severe infections